2004
DOI: 10.1128/aem.70.8.4538-4543.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Caliciviruses

Abstract: The viruses most commonly associated with food-and waterborne outbreaks of gastroenteritis are the noroviruses. The lack of a culture method for noroviruses warrants the use of cultivable model viruses to gain more insight on their transmission routes and inactivation methods. We studied the inactivation of the reported enteric canine calicivirus no. 48 (CaCV) and the respiratory feline calicivirus F9 (FeCV) and correlated inactivation to reduction in PCR units of FeCV, CaCV, and a norovirus. Inactivation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
248
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(269 citation statements)
references
References 41 publications
16
248
1
4
Order By: Relevance
“…However, the detection of viral NA should not be considered detection of noninfectious particles, because, although infectivity cannot be determined, the potential for that microorganism to be infectious before NA extraction cannot be excluded. 47,48 In conjunction with molecular analysis of human enteric viruses, a simple method for the identification of sample inhibition during real-time PCR and RT-PCR assays was also applied. This method uses a commercially available HGV RNA internal standard.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detection of viral NA should not be considered detection of noninfectious particles, because, although infectivity cannot be determined, the potential for that microorganism to be infectious before NA extraction cannot be excluded. 47,48 In conjunction with molecular analysis of human enteric viruses, a simple method for the identification of sample inhibition during real-time PCR and RT-PCR assays was also applied. This method uses a commercially available HGV RNA internal standard.…”
Section: Discussionmentioning
confidence: 99%
“…The virus can also persist in the environment for several days to several weeks on dried surfaces at room temperature, and longer in colder wetter conditions [12,23,24]. Indirect transmission can therefore occur, especially within the close confines of a cattery where secretions may contaminate cages, feeding and cleaning utensils or personnel.…”
Section: Epidemiologymentioning
confidence: 99%
“…Disinfectants are biocide substances that destroy microorganisms or inhibit their activity on inanimate objects or surfaces (McDonnell and Russell 1999). Previous studies (Doultree et al 1999;Duizer et al 2004a;Radford et al 2007) concluded that ethanol and quaternary ammonium-based products were ineffective disinfectants of FCV and the inactivation of FCV required high concentrations of sodium hypochlorite. MNV is sensitive both to alcohols and to bleach and its resistance to basic and acidic pHs as well as it longterm resistance at room temperature is higher than that of FCV (Cannon et al 2006;Belliot et al 2008;Park and Sobsey 2011).…”
Section: Introductionmentioning
confidence: 99%